Review of existing methods of winter concrete - Novak, E. (Ways to Improve Construction Efficiency, 2019)
An overview of the most popular methods of winter concreting; which includes the use of anti-freeze additives; cover concrete mix; heating concrete; electric and infra-red heating and heating of concrete. The concept of "winter conditions" is determined in accordance with the normative documentation. The analysis of the factors influencing the implementation of concreting in winter conditions is carried out. It is revealed that today the demand is to create a methodology for studying deviations of building parameters (cost; durability; labor intensity; etc.) from the planned values under the influence of winter conditions. Identification of factors influencing the construction parameters in the winter; creating the appropriate dependencies is an urgent task of the organization of construction.